Assessment of heat stress in dairy cows related to physiological responses - Kartika Budi Utami; Budi Purwo Widiarso (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2022)
Climate change will continue to occur in the years to come and threaten dairy cows. As a result of climate change, various risks can change due to changing ecological conditions in various places on earth. The study aimed to assess heat stress in dairy cows (calf, heifer, lactating, and dry cow). The heat stress assessment method uses the equation presented by the temperature-humidity index (THI). Heart rate, respiratory rate, and rectal temperature are physiological parameters to determine heat stress. The data collection of cattle's temperature, humidity, and physiological parameters was carried out simultaneously. Data analysis used one-way ANOVA, followed by Tukey's further test. The results of the heat stress assessment showed that the THI values reached 82.8 and 78.2 in the afternoon and evening, causing the calves, lactating cow, and dry cow to be exposed to heat stress. The rectal temperature of the calf increased by 39.10C, the heart rate and respiration rate of lactating cows increased by 66.5-69.2 times/minute and 51.7 times/minute, and the respiration rate of dry cows increased by 49.2 times/minute. Efforts are needed to control heat stress in dairy cows at all age phases so that dairy cows are in comfortable environmental conditions.